Critical points at prescribed energy level for Schrödinger-Bopp-Podolsky systems - Ramos Quoirin, Humberto Rodrigo (2023)
In this note we aim to present an existence result for radial solutions to a Schrödinger-Bopp-Podolsky system in the whole space under the constraint of energy. In particular the problem is depending on a parameter and we ask if, given a priori energy level,for some value of he parameter there is a solution of the system whose energy is the given value. The result is presented in [10] so here just the main ideas are presented, referring the reader to the mentioned paper for all the details and proof.